Appearance as capital : the normative regulation of aesthetic capital accumulation and conversion - Sarpila, Outi; Kukkonen, Lida; Pajunen, Tero; Åberg, Erica (Emerald Publishing Limited, 2021)
The ebook edition of this title is Open Access and freely available to read online. In an era of hyper visuality, service-based labour markets, consumer culture, and times of uncertainty, physical appearance plays an increasingly important role in producing and reinforcing social inequalities. Taking a sociological approach, the authors of Appearance as Capital examine physical appearance as a normatively regulated form of capital and explore how it is possible to accumulate and convert capital based on physical appearance. The chapters examine how norms of accumulating and converting aesthetic capital intertwine with gender, age and other forms of capital and play a role in shaping inequalities. Demonstrating how different cultural, institutional, group-specific and situational norms regulate the possibilities of accumulating and converting aesthetic capital, the authors take a critical stance towards an economics-inspired analysis of physical appearance as universally defined 'beauty' or 'attractiveness' that has standard value for all individuals. By presenting empirical work based in the context of Finnish society, often considered an egalitarian Nordic welfare state, this book provides a fresh perspective on appearance-based inequalities.